Continuum Theory of Active Phase Separation in Cellular Aggregates - Kuan, Hui-Shun; Poenisch, Wolfram; Juelicher, Frank; Zaburdaev, Vasily (Physical Review Letters, 2021)
Dense cellular aggregates are common in biology, ranging from bacterial biofilms to organoids, cell spheroids, and tumors. Their dynamics, driven by intercellular forces, is intrinsically out of equilibrium. Motivated by bacterial colonies as a model system, we present a continuum theory to study dense, active, cellular aggregates. We describe the process of aggregate formation as an active phase separation phenomenon, while the merging of aggregates is rationalized as a coalescence of viscoelastic droplets where the key timescales are linked to the turnover of the active force. Our theory provides a general framework for studying the rheology and nonequilibrium dynamics of dense cellular aggregates.
CRIS-Team WoS Importer:2021-01-22